Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai: Survei pada Pegawai Puskesmas Kersanagara Kota Tasikmalaya - Julmiansah, Yoga; Barlian, Barin; Arif (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This research aims to determine the influence of work motivation and work environment simultaneously or partially on the performance of employees at the Kersanagara Health Center, Tasikmalaya City. The research method used was a quantitative method with a total of 30 respondents. Primary data collection is in the form of a questionnaire. Data analysis in research uses multiple regression analysis. The results of the research show that work motivation and work environment simultaneously have a significant effect on the performance of employees at the Kersanagara Health Center, Tasikmalaya City. Work motivation partially has a significant effect on the performance of employees at the Kersanagara Health Center, Tasikmalaya City. The work environment partially has a significant effect on the performance of Kersanagara Health Center employees in Tasikmalaya City.